Quietly Crowded: Peran Moderasi Kualitas Hubungan Positif di Dunia Maya Terhadap Kesepian dan Subjective Well-Being Masyarakat Perkotaan - Erica, Luisa; Pudjiati, Sri Redatin Retno; Boediman, Lia Mawarsari (Faculty of Psychology, Universitas Surabaya, 2024)
Loneliness is commonly experienced by individuals in urban communities because of the difficulties in establishing close relationships in urban settings. One way to deal with loneliness in the real world is to find virtual friends in cyberspace. In other words, high level of loneliness can cause social relationship in the virtual world to increase and social relationship in the real world to decrease. The social compensation model hypothesized that higher quality interaction with virtual friends could reduce loneliness levels and ultimately increase one's subjective well-being because this interaction is considered a safe relationship and a preference for those who feel isolated. By utilizing the Social and Emotional Loneliness Scale for Adults - Short Version (SELSA-S), the Positive Negative Relationship Quality (PN-RQ) Scale, and the Satisfaction With Life Scale (SWLS), this study found that positive relationship quality in cyberspace (with virtual friends) significantly moderated the association between loneliness levels and subjective well-being (N = 300). Therefore, this study’s results show that not all online interactions are detrimental to individual’s mental health. Also, individuals in urban communities should considering focusing more on increasing the quality of interactions, instead of increasing the quantity or number of friendships.